Análisis, evaluación y control de factores de riesgos mecánicos, físicos en el proceso de comercialización de hierro y material menor de la Empresa ferretería PC Cueva para disminuir el nivel de accidentabilidad.” - Fierro Lara, Adriana Katherine (2022)
Risk Reduction is one of the actions that in a company, whatever its nature, must be essential to ensure adequate care of the workers who collaborate in the daily work within the care and action of its own activities that are generated in the company, which helped me to carry out an adequate approach to the problem, making a precise contextualization of it that led me to make a more precise formulation, which allows us to know the reality plus the information collected from the primary source, it facilitated me to have a close knowledge of the reality of the physical and work environment of the company to be able to propose actions to provide security both to its workers and to the people who come to it to acquire goods. In order to carry out what has been stated, we must know the risks to which we are exposed during the working day, once known and weighed, we must prepare a corresponding plan to mitigate these risks to reduce them to a minimum or cancel them if possible, with this we will be improving the work environment of the aforementioned company. For the collection of information, there was sufficient predisposition and support from the Manager and the Workers of the company, which facilitated the work and served to achieve the results of our objectives as demonstrated in chapter IV of the work, which It results in the direct benefit of the company's workers and this benefit results in the benefit of the entire company because it has an adequate and professionally prepared document, which will allow greater job security. To identify the risks and weigh them, we have opted for the application of the Technical Note on Prevention 330 (NTP330) methodology, which is a Spain regulation prepared by the National Institute of Occupational Safety and Hygiene (INSHT), which I have had to adapt to